PENGEMBANGAN BUKU AJAR PENGANTAR PENDIDIKAN DENGAN MUATAN NILAI ISLAM - Ervika Dewi Wahyuni; Rizka Nanda Prasetyo (STAI Ma'had Aly Al-Hikam Malang, 2022)
The purpose of this study was to determine the development of introductory educational textbooks and test the feasibility of introductory educational textbooks with Islamic values at the Balitar Islamic University. The research steps in the modified development model are eight: (1) collection of information as data for needs analysis, (2) planning, (3) product design development, (4) design validation (5) product revision, (6) trial product (7) product revision, (8) production of textbooks. The research instrument used the interview method. The results of the validation on media experts got an average of 3.5 which was stated in the good category. The results of the validation of the material experts got an average of 3.2 which was stated in the good category . The validation results for linguists got an average of 3.43 which was stated in the very good category.